A new general formulation of a transfer-function matrices of 2D digital systems. Issue 2 (3rd April 2019) - Bouhamla, Lakhdar; Adamou-Mitiche, Amel Baha Houda; Mitiche, Lahcène
ABSTRACT: The contribution of our paper is a new simple method for transfer-function matrices derivation in two-dimensional digital systems from Roesser's model is given. The main idea of this method is changing the form of the transfer-function, from state space to a fraction with a polynomial numerator and denominator. Then by identity, we can derive matrices of numerator and denominator. Numerical examples are given to prove the effectiveness and the simplicity of the proposed method.